A method of requirements elicitation and analysis for Global Software Development. Issue 4 (27th October 2016) - Ali, Naveed; Lai, Richard
Abstract: To perform requirements elicitation and analysis, effective communication and collaboration between stakeholders are necessary. Global Software Development (GSD), where software teams are located in different parts of the world, has become increasingly popular. However, geographical distance, cultural diversity, differences in time zones, and language barriers create difficulties for GSD stakeholders in engaging in effective communication. Taking into consideration the factors involved in GSD, previous research showed that the ways by which requirements are gathered and analyzed for collocated software development cannot be used effectively for GSD. Thus, in this paper, we present a method of requirements elicitation and analysis for GSD. The method consists of 4 stages: (1) data collection; (2) educating stakeholders about GSD issues; (3) post‐education assessment; and (4) requirements elicitation and analysis. Past researchers used student groups in a university environment to play the roles of stakeholders in experiments in GSD studies. Likewise, we preliminarily validate our method by applying it to a case study of an online shopping system, where the roles of client, requirements engineer, project analyst, and designers were played by a group of students.